Between Liberalism and Nationalism in Mexico: the Economic Thought of José Yves Limantour - Quintanar Zárate, Iliana Marcela (2015)
The objective of this paper is to ascertain the principles of the economic thinking of José Yves Limantour, and the changes they underwent, to explain the process of transformation of econo- mic liberalism which, as will be seen, tended more toward state intervention; this, incidentally, can be considered as the basis of economic nationalism as developed by the post-revolutionary governments. It follows, then, that the study of Limantour and his economic thinking seeks to explain the transformation process to which the Mexican liberal state was subjected in thelast decade of the 19th century and the first decade of the 20th. The study is divided into two sections, the first of which explores the general characteristics of the liberal state and its transfor- mations from the 1850s through to the 1900s. The second analyses the spheres of the Mexican economy that constituted the main focuses of Limantour’s interventions and regulation.